CT scan incidental findings in trauma patients: does it impact hospital length of stay?. Issue 1 (14th September 2017) - Andrawes, Peter; Picon, Antonio I; Shariff, Masood A; Azab, Basem; von Waagner, Wolf; Demissie, Seleshi; Fasanya, Charles
Abstract : Background: CT scans are heavily relied on for assessment of solid organ injuries complementing clinical examination. These CT scans could also reveal pathologies not related to trauma called incidental findings. We aimed to evaluate the frequency of these findings and their outcome on hospital services. Methods: A retrospective chart review of prospectively collected data of the emergency department's trauma database from January 2005 to December 2011 to evaluate incidental findings on CT scans on trauma admissions. These incidental findings were divided into three classes: class 1—minor degenerative, non-degenerative, normal variants or congenital finding that does not require further investigation or workup; class 2—findings not requiring urgent intervention with scheduled outpatient follow-up and class 3—all findings that require urgent evaluation/further investigation during the same hospital admission. One-year follow-up was done to review hospital length of stay, trauma clinic follow-up and post-trauma surgery. Results: Of 1000 charts reviewed, 957 were selected after 43 patients were excluded due to incomplete documentation. Of the 957 patients, 385 (40%) were found to have incidental findings. A total of 560 incidental findings were found on the CT scan reports with one-third of patients having multiple findings (144 patients, 37.4%). The largest number of incidental findings were in class 2. The incidental group had significantly longer length of stay after adjusted multivariate analysis (8.7±0.48 vs 6.7±0.55, p=0.005). Conclusion: The incidental findings are commonly found during CT imaging in trauma centers and our rate was 40%. Appropriate documentation, communication and follow-up of those findings is necessary. A classification system for these findings practiced nationwide will aid in categorizing the urgency of continued follow-up. This also will help decrease the length of hospital stay and healthcare cost. Level of evidence: Level 4